Verónica Rueda Estrada. Recompas, recontras, revueltos y rearmados. Posguerra y conflictos por la tierra en Nicaragua 1990-2008 (Palimpsesto, 2016)
Verónica Rueda Estrada. Recompas, recontras, revueltos y rearmados. Posguerra y conflictos por la tierra en Nicaragua 1990 - 2008